A digital twin-driven hybrid approach for the prediction of performance degradation in transmission unit of CNC machine tool. (February 2022) - Yang, Xin; Ran, Yan; Zhang, Genbao; Wang, Hongwei; Mu, Zongyi; Zhi, Shengguang
Highlights: DT model based meta-action, collected data from multi-sensors on transmission unit. Monitoring and simulation of performance degradation on the wear of transmission. Combining the data-driven and the model-based method by particle filter algorithm. Integrating mechanism and real-time data, mutual modified to a High fidelity model. Abstract: Precision performance prediction of transmission system is considered as a key technology to modern equipment health management. Given the importance of maintaining a transmission system's precision, this paper presents a hybrid approach framework driven by digital twin technology (DT), to predict performance degradation. Firstly, a DT model based on meta-action theory is established, and real-time monitoring and digital simulation, driven by DT data, is realized in order to analyze the precision of the transmission units in machine tools. Secondly, the wear of gear in transmission unit is studied through Achard wear theory, which considered the comprehensive influence of gear load and speed on surface wear of the gear pair tooth, based on the model driving method. The performance degradation of the transmission unit is obtained by using the RBF neural network algorithm based on the data-driven method to extrapolate the wear data to the field-measurable precision index value. In addition, the hybrid predictive approach of the performance degradation model through the particle filter algorithm is built, and the real-time data is used to update the current state estimation to improve the prediction accuracy. By combining the mechanism of the physical degradation processes with the real-time and historical data and turning them into a cooperative architecture, this prediction method uses the complementary advantages offered by the fusion of these methods to bridge the link between data-driven prediction and model-based prediction. Finally, the method has been successfully applied to the precision prediction of the transmission unit in CNCMT turntable, and it is compared with the single prediction method to verify the effectiveness and feasibility.